Etika dan Profesi Hakim Terhadap Regulasi Penegakan Hukum di Negara Republik Indonesia - Muhamad Auza Syam; Kayus Kayowuan Lowoleba (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
The judge's code of ethics regulates the conduct of judges, ensuring quality through integrity, discipline, and justice. This article explores the interconnection between ethics, the judge's profession, and law enforcement regulations in Indonesia, referencing laws like the National Police, Advocates, and Prosek. Judges must comprehend and adhere to these regulations for law-compliant decisions. The code of ethics comprises 10 principles, guiding judges with values like honesty and fairness. The article addresses two issues: the impact of law enforcement regulations on the judge's profession quality in Indonesia and the consequences of violating the judge's code of ethics on legal supremacy. The goal is to comprehend law enforcement regulations and the repercussions of breaching judges' codes of ethics. The research methodology used is normative juridical, identifying factors in legal rules, doctrine, and principles for problem solutions. The article concludes that law enforcement regulations significantly influence the judge's profession's quality, emphasizing independence, integrity, and fair application of the law. Challenges, including political pressure and corruption, require comprehensive solutions. Violations of the judge's code of ethics, exemplified by cases like M. Akil Mochtar's, can harm legal supremacy by tarnishing the judiciary's image. The conclusion underscores the pivotal role of law enforcement regulations in upholding the judging profession's quality in Indonesia. Enhancing preventive measures and addressing violations of the judge's code of ethics are imperative to preserve the judiciary's integrity and professionalism.